2017
DOI: 10.3390/genes8020077
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Expression Profile Identifies High Grade, Non-Muscle-Invasive Bladder Tumors at Elevated Risk to Progress to an Invasive Phenotype

Abstract: The objective of this study was to identify a panel of microRNAs (miRNAs) differentially expressed in high-grade non-muscle invasive (NMI; TaG3–T1G3) urothelial carcinoma that progress to muscle-invasive disease compared to those that remain non-muscle invasive, whether recurrence happens or not. Eighty-nine high-grade NMI urothelial carcinoma lesions were identified and total RNA was extracted from paraffin-embedded tissue. Patients were categorized as either having a non-muscle invasive lesion with no eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…miR-203a-3p in liver cancer and bladder cancer was up-regulated [33, 34], and the expression of other miR-203 family members could be up-regulated in cervical cells [35]. Other studies have shown that the expression of miR-203a-3p was down-regulated in nasopharyngeal carcinoma [23].…”
Section: Discussionmentioning
confidence: 99%
“…miR-203a-3p in liver cancer and bladder cancer was up-regulated [33, 34], and the expression of other miR-203 family members could be up-regulated in cervical cells [35]. Other studies have shown that the expression of miR-203a-3p was down-regulated in nasopharyngeal carcinoma [23].…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNA (miRNA) is an important class of small ncRNA that induces the translation inhibition and degradation of target mRNA through targeting the mRNA 3-untranslated region (3′-UTR) [ 12 ]. MiR-32-5p is an important mediator that is closely related to cancer-specific survival of bladder tumors [ 13 ]. MiR-32-5p was down-regulated in blood from prostate cancer patients, and thus was expected to be a new indicator for prostate cancer diagnosis [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lenherr found abnormal expression between progressors and non-progressors for several miRNAs including miR-205-5p and miR-20a-5p. Some of the known targets of miR-205-5p include ZEB1/2 , PTEN , and VEGFA [32]. The downregulation of miR-205-5p has been linked to the epithelial-mesenchymal transition (EMT) and has been significantly associated with progression in non-muscle invasive BC.…”
Section: Discussionmentioning
confidence: 99%